2020
DOI: 10.1002/mc.23191
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in PDSS1 and SLC16A6 of the ketone body metabolic pathway predict cutaneous melanoma‐specific survival

Abstract: A few single-nucleotide polymorphisms (SNPs) have been identified to be associated with cutaneous melanoma (CM) survival through genome-wide association studies, but stringent multiple testing corrections required for the hypothesis-free testing may have masked some true associations. Using a hypothesis-driven analysis approach, we sought to evaluate associations between SNPs in ketone body metabolic pathway genes and CM survival. We comprehensively assessed associations between 4196 (538 genotyped and 3658 im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…A multicenter study found that SLC16A5 gene mutation was associated with adverse reactions to platinum-based drugs in testicular cancer patients, which provided a reference for the mechanism of adverse reactions in testicular cancer [ 46 ]. Wei et al found that upregulation of SLC16A6 affects patient outcomes through ketone body transporter pathways [ 47 ]. Studies of SLC16A7 have focused on prostate cancer and are associated with the malignant transformation of prostate cancer cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter study found that SLC16A5 gene mutation was associated with adverse reactions to platinum-based drugs in testicular cancer patients, which provided a reference for the mechanism of adverse reactions in testicular cancer [ 46 ]. Wei et al found that upregulation of SLC16A6 affects patient outcomes through ketone body transporter pathways [ 47 ]. Studies of SLC16A7 have focused on prostate cancer and are associated with the malignant transformation of prostate cancer cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several biomarkers or techniques detecting specific chromosomal sequence abnormalities have been proposed for melanoma susceptibility, prognosis, and recurrence. These include SNPs of metabolic pathway genes [4], CD28/CTL4/ICOS genes [5], the Tyrosinase gene [6], VDR genes [7], and PI3K genes [8]. This has allowed the definition of several SNP signatures for melanoma prognosis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“… 5 Several studies showed that PDSS1 speed up the progression of some tumors, such as cutaneous melanoma, bladder cancer, breast cancer, and HCC. 6–11 Bioinformatics studies suggest that PDSS1 may be associated with hypoxia in the tumor microenvironment of HCC. 9–11 However, it is not yet clear whether PDSS1 acts as a prognostic marker in HCC and if its expression is related to the tumor immune infiltration.…”
Section: Introductionmentioning
confidence: 99%